THINKING LEAN: Improving Vitreoretinal Clinic Efficiency by Decentralizing Optical Coherence Tomography. Issue 2 (February 2016) - Callaway, Natalia F.; Park, Joyce H.; Maya-Silva, Jacqueline; Leng, Theodore
Abstract : Purpose: Patients in vitreoretinal clinic have long wait times that could be reduced by improving the efficiency of patient flow. The objective of this study was to determine whether decentralizing optical coherence tomography (OCT) into the technicians' room would reduce patient wait times and improve clinic efficiency. Methods: Randomized, single-center, clinical trial for 1 month without follow-up at Byers Eye Institute at Stanford. Subjects were return patients of three vitreoretinal specialists in March 2013. The intervention consisted of decentralizing OCT devices from the central photography suite into the technician screening rooms. Total clinic times and total wait times throughout subject appointments were recorded and compared with the control group (centralized photography suite). Secondary outcomes included frequency of injections, procedures, and primary diagnosis codes. Results: Decentralized OCT reduced patient wait times by 74% and reduced total clinic appointment time by 36%. Subjects in the intervention arm experienced significantly reduced total wait time (mean difference = 15.9 minutes, P < 0.0001) and total time in clinic (mean difference = 22.9 minutes, P < 0.0001). Conclusion: Decentralized OCT represents the application of lean process concepts to improve vitreoretinal clinic efficiency. Decentralized OCT reduced both the total wait time and total time in clinic for return patients in a vitreoretinal clinic. Abstract : Patients experience long wait times in vitreoretinal clinics that could benefit from the application of lean process techniques. In this study, we decentralize optical coherence tomography devices to technician rooms and compare it to the usual care. We report significantly reduced total wait time and clinic time for patients.